Peradilan In Absentia bagi Pelanggar Lalu Lintas yang Berkeadilan - Dunggio, Haklainul; Sugiri, Bambang; Syafa'at, Rachmad (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This study discusses in absentia trial system for traffic violations in Indonesia, proofing in traffic violations, and whether or not there is a need to prove errors in traffic violations. This study uses a normative juridical method with a legislative approach. The regulation of in absentia trial system has three requirements. First, absolute in absentia trial system. Second, the judge examines, adjudicates, and decides cases without the presence of the offender. Third, the offender is not called to attend the trials. Proofing of traffic violations has resulted from a valid evidence coupled with the judge's conviction. The faults of offenders in traffic violations must still be proven, not enough just by action.